Study on Polymorphisms of OsHKT2;4 Gene in some Vietnamese Rice - Dat, Nguyen Tien; Phuc, Do Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Salt stress leads to serious inhibiting of the growth and development of plants. The selection and generation of plants resistant to salinity is effective and sustainable way to overcome the saline soil. It has been proven that the HKT transporter is involved in salinity tolerance in plants. OsHKT2;4 gene is a member of class II of HKT gene family in rice encoding protein  which mediates Na + -K + cotransport and at high Na + concentration preferred Na + -selective transport. In this study, the natural variations in OsHKT2;4 gene sequence was investigated in some Vietnamese rice cultivars. The full length of gene sequence was amplified by PCR, followed by direct sequencing of PCR product. Analysis of obtained sequences among cultivars revealed the 11 single nucleotide polymorphisms, consisting of 8 sites in exons and 3 sites in intron. Further analysis showed that these 8 substitutions in exons were non-synonymous which caused changes in amino acids at signal peptide (S11F and N17T), at the loop (T66V, T84I, S133L, S342N) and the transmembranes (V53M, L253F). Keywords : Genetic polymorphism, HKT, rice, OsHKT2;4 .